Prevalence and management of anemia in pre-dialysis Malaysian patients: A hospital-based study - Salman,Muhammad (2016)
Summary Objective: Anemia, a common complication of chronic kidney diseases (CKD), is involved in significant cardiovascular morbidity. Therefore, the objective of our study was to investigate the prevalence and severity of anemia in pre-dialysis patients, as well as to determine the predictors of anti-anemic therapy. Method: A retrospective, observational study was conducted on adult pre-dialysis patients receiving treatment at the Hospital Universiti Sains Malaysia from January 2009 to December 2013. Results: A total of 615 eligible cases were included. The mean age of patients was 64.1±12.0 years. The prevalence of anemia was 75.8%, and the severity of anemia was mild in 47.7% of the patients, moderate in 32.2%, and severe in 20%. Based on morphological classification of anemia, 76.9% of our patients had normochromic-normocytic anemia whereas 21.8 and 1.3% had hypochromic-microcytic anemia and macrocytic anemia, respectively. Oral iron supplements were prescribed to 38.0% of the patients and none of the patients was given erythropoietin stabilizing agents (ESA) or intravenous iron preparations. In logistic regression, significant predictors of anti-anemic preparation use were decreased hemoglobin and hematocrit, and advanced stages of CKD. Conclusion: The results of the present study suggest that the prevalence of anemia in pre-dialysis patients is higher than currently accepted and it is found to be correlated with renal function; prevalence increases with declined renal function. An earlier identification as well as appropriate management of anemia will not only have a positive impact on quality of life but also reduce hospitalizations of CKD patients due to cardiovascular events.